2015
DOI: 10.1093/ckj/sfv110
|View full text |Cite
|
Sign up to set email alerts
|

Hints to the diagnosis of uromodulin kidney disease

Abstract: BackgroundUromodulin kidney disease (UKD) is an inherited kidney disease caused by a uromodulin (UMOD) gene mutation. The UMOD gene encodes the Tamm–Horsfall protein (THP), which is the most abundant protein in healthy human urine. Because of its rarity, the incidence of UKD has not been fully elucidated. The purpose of the present study is to clarify the frequency of UKD among patients who underwent renal biopsy.MethodsImmunostaining for THP was performed for patients <50 years of age with renal insufficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Uromodulin is essential protein encoded by UMOD gene and produced in the kidney and contribute to colloid osmotic pressure, retards passage of positively charged electrolytes, prevents urinary tract infection and modulates formation of supersaturated salts and their crystals. 16,17 In the present study we identified 9 patients (5 were relatives) with AMOD gene mutation and our prior hypothesis, patients with UMOD gene mutation have more deterioration effects than others. These worsening effects may lead to hemodialysis impaired control of nitrogenous wastes and minerals.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Uromodulin is essential protein encoded by UMOD gene and produced in the kidney and contribute to colloid osmotic pressure, retards passage of positively charged electrolytes, prevents urinary tract infection and modulates formation of supersaturated salts and their crystals. 16,17 In the present study we identified 9 patients (5 were relatives) with AMOD gene mutation and our prior hypothesis, patients with UMOD gene mutation have more deterioration effects than others. These worsening effects may lead to hemodialysis impaired control of nitrogenous wastes and minerals.…”
Section: Discussionsupporting
confidence: 51%
“…UMOD gene mutation also associates with serum urea (P=1.0x10(-6)), uric acid (P=0.0064). 17,18 Although, several studies have suggested that the level of uromodulin in the urine could represent a valuable biomarker for the development of CKD, 19 but we suggest the use of the levels of nitrogenous products during dialysis as indicators of UMOD gene mutation. Such patients with constant biomarkers elevation can be further submitted to gene analysis.…”
Section: Discussionmentioning
confidence: 88%
“…Case #3 was one of 15 patients with renal insufficiency, hyperuricemia and normal urine tests without glomerular abnormalities under 50 years old extracted from the 3787 patients. Abnormal UMOD accumulation was detected in the kidney of case #3, and subsequently UMOD mutation was detected [13]. Another patient without a family history (case #9) was suspected to have ADTKD from the clinical history and kidney pathological findings which prompted genetic testing.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations have demonstrated decreased urinary THP excretion in endemic nephropathy [ 81 , 82 ], diabetic nephropathy [ 54 , 56 , 70 ], and lupus nephritis [ 53 ]. The decreased urinary THP production is not only a useful biomarker of renal tubular damage [ 56 , 57 , 58 ] but also an indicator of decreased clearance of systemic and renal proinflammatory cytokines, and it can thus accelerate renal inflammation.…”
Section: Pathological Conditions Related To Abnormal Thp Expressiomentioning
confidence: 99%